2011
DOI: 10.1016/j.cmpb.2010.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Metal artifact reduction in dental CT images using polar mathematical morphology

Abstract: ElsevierNaranjo Ornedo, V.; Lloréns Rodríguez, R.; Alcañiz Raya, ML.; López-Mir, F. (2011). Metal artifact reduction in dental CT images using polar mathematical morphology. Computer Methods and Programs in Biomedicine. 102 (1) AbstractMost dental implant planning systems use a 3D representation of the CT scan of the patient under study as it provides a more intuitive view of the human jaw. The presence of metallic objects in human jaws, such as amalgam or gold fillings, provokes several artifacts like streak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 14 publications
0
19
0
2
Order By: Relevance
“…39 Implants, dental reconstructions and orthodontic appliances may cause beam hardening and streaking artefacts, thus decreasing image quality. 40 To determine image quality in our study, we have evaluated the number of NASs due to metallic dental reconstructions. The results show that, compared with the CBCT scans, MDCT scans showed more NASs because of the close proximity of the measured area to the metal reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…39 Implants, dental reconstructions and orthodontic appliances may cause beam hardening and streaking artefacts, thus decreasing image quality. 40 To determine image quality in our study, we have evaluated the number of NASs due to metallic dental reconstructions. The results show that, compared with the CBCT scans, MDCT scans showed more NASs because of the close proximity of the measured area to the metal reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…More elaborate strategies include monoenergetic processing of dual-energy CT data, which works nicely for surgical plates and implants, 11,12 but its effect is limited with dental hardware. Sinogram in-painting methods 8,13,14 and iterative, 15,16 statistical, 17,18 and filtering methods 13,19 have been suggested, but for various reasons, they have not made their way into clinical practice. NMAR is an in-painting-based MAR method that is designed to reduce metal artifacts and to prevent the introduction of new artifacts by replacing raw data from the metal trace more reliably.…”
Section: Discussionmentioning
confidence: 99%
“…Metallic implants generate metal artefacts on CT and MRI, which can be reduced to some extent using postprocessing algorithms (13) and specific scanning protocols (14,15). A recent study by the authors quantifying metal artefacts had reported that if metal screws are ~2 or ~3 mm away from the ankle joint for CT and MRI respectively, a clear visualisation of the ankle joint can be obtained (16).…”
Section: Original Articlementioning
confidence: 99%